Jeffrey W. Aernie, Is Paul also among the Prophets? An Examination of the Relationship between Paul and the Old Testament Prophetic Tradition in 2 Corinthians (LNTS 467; London – New York: T&T Clark 2012) - Kowalski, Marcin (The Biblical Annals, 2017)
Book review: Jeffrey W. Aernie, Is Paul also among the Prophets? An Examination of the Relationship between Paul and the Old Testament Prophetic Tradition in 2 Corinthians (LNTS 467; London – New York: T&T Clark 2012). Pp. XV+296. 136. ISBN 9780567175724 (hardback).